2018
DOI: 10.17756/jocd.2018-015
|View full text |Cite
|
Sign up to set email alerts
|

Ecological Determinants of the Happiness Index, Life Expectancy, Incidence and Dietary Patterns in Different Countries

Abstract: There is a growing interest to the Happiness Index in the world. Purpose of this study is an analysis of the impact of income, UV and latitude on the Happiness Index, incidence and dietary patterns in different countries. Using the Mann-Whitney criterion, it is established that income is 20 times higher in happy countries, and their geographic location is 35 ° to the north of not happy countries (p = 0.001). In the happy countries people live 27 years longer, more rarely suffer from cardiovascular diseases, di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
8
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 19 publications
5
8
0
Order By: Relevance
“…In MC compared to CC the burden of melanoma is 3 times higher, and the burden of multiple sclerosis is 1.5 times higher. These data are quite in line with common views [38]. MC have higher levels of total consumption, consumption of animal products, and alcoholic beverages than CC.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In MC compared to CC the burden of melanoma is 3 times higher, and the burden of multiple sclerosis is 1.5 times higher. These data are quite in line with common views [38]. MC have higher levels of total consumption, consumption of animal products, and alcoholic beverages than CC.…”
Section: Discussionsupporting
confidence: 90%
“…We have shown that cardiovascular diseases depend on income and do not depend on geographic latitude [37]. And diabetes does not depend on income, but depends on geographic latitude [38]. In MC compared to CC the burden of melanoma is 3 times higher, and the burden of multiple sclerosis is 1.5 times higher.…”
Section: Discussionmentioning
confidence: 84%
“…The fact is that in every country in the world, including Mediterranean countries, there is a large number of diseases, more than 220 nosological forms. For example, the burden of cardiovascular diseases is higher, the lower per capita income in countries [56]. At the same time, the frequency of leukemia in countries is higher, the higher the per capita income, as our studies show.…”
Section: Discussionsupporting
confidence: 76%
“…In population studies [14,56], we showed that the incidence of many diseases, indicators of quality of life, MS and NS depend on different income per capita and geographical latitude. This complicates the assessment of risk factors.…”
Section: Overweight and Obesity As The Risk Factors For Leukemia In The Mediterranean Countriesmentioning
confidence: 99%
See 1 more Smart Citation